Effect of Seed Priming on Maize in the Western Hills of Nepal - Koirala, Keshab Babu (International Journal of Applied Sciences and Biotechnology, 2017)
With a view to identify the effect of seed priming technology on maize in the western hills of Nepal, five different varieties of maize including farmers' local were tested during summer seasons of 2004 at three sites of Gorkha, Palpa and Myagdi districts using mother-baby scheme with primed and non-primed treatments. Results of mother trials combined over locations revealed that primed treatments silked three days earlier and matured six days prior to non-primed counterparts. Significant increase in grain yield, average of 11.6% and maximum of 27.8% was recorded. Farmers' response in baby trials combined over locations showed that plant stand after germination in primed treatment was found better as reported by 80% of the respondents. Int. J. Appl. Sci. Biotechnol. Vol 5(4): 470-478